Tinta Alami Berbasis Ekstrak Bit, Pektin dan Kitosan: Potensi Sebagai Alternatif Tinta Ramah Lingkungan - Muryeti, Muryeti; Fachturozi, Nizar Ikhwanul (Rekayasa Material, Manufaktur dan Energi, 2026)
The growth of the food and packaging industry demands the use of printing inks that are safe for both health and the environment, while conventional inks still contain heavy metals and volatile organic compounds (VOCs) that pose risks of irritation and pollution. Natural components such as beetroot extract, pectin, and chitosan have potential to produce eco-friendly inks; however, previous studies remain partial and lack comprehensive formulations. This study aims to formulate bio ink based on beetroot extract, orange peel pectin, and chitosan as a sustainable printing alternative. A total of 24 formulations were tested with chitosan (0–5 mL) and beetroot extract (4–8 g) at 60 °C and 80 °C. Results showed viscosity ranged from 27.983–117.667 s at 60 °C and 12.31–104.357 s at 80 °C, with chitosan significantly acting as a thickening agent. Solid content was 98.103–99.597% (60 °C) and 97.527–99.360% (80 °C), with lower chitosan levels yielding higher stability. Color analysis revealed L* decreased with increasing beetroot extract (83.710–88.087 at 60 °C; 75.847–85.743 at 80 °C), a* increased especially in K5B8 (11.443–18.840), while b* shifted from –6.500 to +0.893. ΔE values ranged from 2.13 (K1B6, most stable) to 12.49 (K5B8, least stable). These findings confirm that chitosan and beetroot extract strongly influence viscosity, solid stability, and color intensity, supporting the development of eco-friendly natural inks.